Penerapan Media Pembelajaran Smart Box Karapan Sapi sebagai Upaya Pengenalan Budaya Lokal Madura di SDI Al Aziziyah - Avisenna, Emilda Shofiyah; Darma, Achmad Yahya Adi; Maharani, Icha Berliana Putri; Ainiyah, Qurotul; Khotimah, Khusnul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to address the conventional approach to local content learning at SDI Al Aziziyah, which leads to boredom and low student participation. The Karapan Sapi tradition, a Madurese cultural tradition, holds significant educational value, but has not been presented interactively in learning. Therefore, a multisensory Smart Box Karapan Sapi media was developed using a qualitative-descriptive approach. Data were obtained through observation, interviews, and questionnaires to analyze needs, the design process, and initial user responses. The results showed that the Smart Box received very positive responses from teachers and students because it was able to present cultural learning in a more engaging, contextual, and interactive manner. This media is considered to have the potential to increase cultural literacy and be an effective strategy in preserving local cultural heritage in elementary education